La obra de arte y su función crítica de la realidad - Simancas Lalangui, Cristian Javier (2017)
The visual arts in the path of the s of the twentieth century were generating radical changes unlike those process that had been developed throughout the period of modern art. The dizzying transformations at this time between an artistic movement and another were noticing since the early 19th century; thus in the first decades we have, Cubism, Futurism, Dada, Surrealism, among others that were part of the postmodern art stage. The present study tries to create a brief tour of some of the above-mentioned processes to understand the intentions of both the use of materials such as in the use of the concepts for creating an artistic element that is able to question their reality and cause ruptures in the social systems from its symbolic function. Thus, we have to get to the point where art is of very strong philosophical and theoretical aspects to strengthen his speech and be able to break into the public arena with increased power questioning; to do this we have to mention the contemporary art that is the fundamental element in the development of the artistic proposal aim of the present study. Thus, the art at this time becomes diverse, its processes, and its concepts are heterogeneous and act in response to their environment, assuming an important role in the development of the current society, to the point that it is unthinkable that it can exist without art, because this gives us the possibility of generating symbolic processes necessary for the integral growth of individuals under perspective and taking advantage of the political moment in the country, it is proposed a work that question and talk to us in a symbolic way how, from the discourse and political action the sense of nationalism is used to achieve power, regardless of even the mass that makes up all of the Ecuadorian society.